PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN THINK PAIR SHARE DALAM PEMBELAJARAN IPS KELAS V - Rosis, Pretty Rozalia; Asran, Mastar; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractA common problem in this study is How does the use of the cooperative model of think pair share in social science learning can improve student learning outcomes in grade V of Elementary School 9 Pontianak Barat. The research method used in this research is descriptive method, the form of research is classroom action research and the nature of this research is collaborative. This research was conducted for three cycles with the results obtained that is 1) the ability of teachers in planning learning by using a think pair share type from cycle I is 3.08, cycle II 3.7, cycle III 3.87. 2) the ability of teachers in the implementation of learning using think pair share type from cycle I is 3.33, cycle II 3.58, cycle III 3.86. 3) student learning outcomes using think pair share type starting from cycle I that is 74,32, cycle II 82,43 and cycle III 93,78. With the results obtained show that using the think pair share type in learning Citizenship Education can improve the learning outcomes of fifth graders Elementary School 9 Pontianak Barat. Keywords: Learning outcomes, Think pair share